Mineralocorticoid receptor antagonist pretreatment to MINIMISE reperfusion injury after ST-elevation myocardial infarction (The MINIMISE STEMI Trial): Rationale and Study Design - Bulluck H. (John Wiley and Sons Inc., 2016)
Clinical Cardiology